Determinants of implanon discontinuation among women in Gedeo Zone, South Ethiopia: a case-control study - Tihtina Bezabih; Selamawit Dires Agidew; Selamawit Semagn Kebede; Moges Mareg Belay; Ever Siyoum; Eden Ashenafi; Mahlet Birhane (BMC, 2024)
Abstract Background The main public health problem that has a significant impact on the high fertility rate, unintended pregnancies, and induced abortion is Implanon cessation. In addition to Implanon being underutilized in Ethiopia, the rate of cessation is higher among women who started using it. Nevertheless, little is known about the factors that lead to Implanon cessation. Objectives The study was aimed to determine the factors that led women to discontinue Implanon in Gedeo Zone, Southern Nation Nationalities and Peoples Region, southern Ethiopia, 2019. Method A community-based unmatched case-control study design was carried out. Cases and controls were selected by a multi-stage sampling with a 1:2 case-to-control ratio. Data was entered into EPi-data version 3.1 and exported to Statistical Package for Social Sciences (SPSS) version 20 for analysis. A bivariate and multivariable logistic regression was used to identify the factors affecting Implanon discontinuation. The adjusted odd ratio (AOR) with 95% Confidence Interval (CI) was used to determine the precision of estimates, and statistical significance was declared at a p-value of 0.05. Result From 516 women included in to the study, 495 (cases = 166 and controls = 329) women have responded to the questionnaires making a response rate of 96%. Monthly income 500-1000 birr [AOR: 0.3; 95% CI (0.2-0.5)], above 1000 birr [AOR: 0.2; 95% CI (0.1-0.4)], history of abortion [AOR: 2.0; 95% CI (1.0-4.1)], birth spacing [AOR: 0.6; 95% CI (0.3-0.9)], partner objection [AOR: 2.4; 95% CI (1.4-4.2)] were significantly associated factors. Conclusion This study identified that monthly income, having abortion history, birth spacing, partner objection were the factors that affect Implanon discontinuation. To reduce implanon discontinuation, reducing abortion, involving partner and increasing the birth spacing, appropriate counseling before the insertion and appropriate follow-up by a health care practitioner are highly recommended.